Effects of Climate Warming on Consumer-Resource Interactions: A Latitudinal Perspective - Amarasekare, Priyanga (Frontiers in Ecology and Evolution, 2019)
There is increasing evidence that climate warming is impacting biodiversity by disrupting species interactions. Trophic (consumer-resource) interactions, which comprise the fundamental units (modules) of food webs, are of particular importance because they have an intrinsic tendency to fluctuate in abundance, thus running to risk of stochastic extinction during periods of low abundances. Here I present a mathematical framework for predicting warming effects on consumer-resource interactions. This work differs from previous theory in two ways. First, it uses delay differential equations to realistically depict the developmental delays inherent in ectotherm life cycles, and incorporates mechanistic descriptions of phenotypic trait responses, derived from first principles of thermodynamics, into the dynamical delay model. Second, it tests the latest IPCC predictions on warmer-than-average winters and hotter-than-average summers. I investigate warming effects on three major axes: latitude (tropical vs. temperate), life stage attacked (juvenile vs. adult), and nature of consumer-resource dynamics in the absence of temperature variation (stable vs. complex). I report three findings. First, consumer-resource interactions in the tropics are more at risk of species losses due to warming while those in the temperate zone are more at risk of extreme fluctuations in species' abundances. Second, effects of warming are more detrimental when the consumer attacks the adult stage of the resource and when consumer-resource interactions exhibit complex dynamics. Third, hotter-than-average summers are more detrimental to consumer-resource interactions than warmer-than-average winters. I discuss implications of these results for biodiversity and biological pest control.